Analysis of Training, Self-Efficacy, and Discipline on Employee Performance Mediated by Employee Engagement: A Study in Freight Forwarding - Susanto, Primadi Candra; Murdiono, Jatmiko; Susita, Dewi (Bulletin of Counseling and Psychotherapy, 2025)
This research aims to see the influences that cause increased performance. The research method used is Quantitative Descriptive. The data used is primary data, obtained from a questionnaire instrument with a Likert scale measurement scale of 1-5 (strongly disagree-strongly agree), filled in by employees at 6 freight forwarding companies in Jakarta, Indonesia. The sampling technique used purposive sampling with a sample size of 108 participants. The analysis software utilized is SmartPLS 4.1.0.0. The results are: 1) Training and self-efficacy have a positive and significant effect on employee engagement; 2) Discipline has no positive and insignificant effect on employee engagement; 3) Training has a positive and significant effect on employee performance; 4) Self-efficacy and discipline have no positive and insignificant effect on employee performance; 5) Employee engagement has a positive and significant effect on employee performance; 6) Training and self-efficacy have a positive and significant effect on employee performance throughout the employee's existence; and 7) Discipline has no positive and insignificant effect on employee performance through the presence of employees. To improve employee performance, it is supported by providing continuous training